2001
DOI: 10.1002/cne.1191
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the melanin‐concentrating hormone (MCH) receptor mRNA in the rat brain

Abstract: The melanin-concentrating hormone (MCH) system is thought to be an important regulator of food intake. Recently the orphan G protein-coupled receptor SLC-1 was identified as the MCH receptor (MCHR). Preliminary analyses of MCHR mRNA distribution have supported a role for the MCH system in nutritional homeostasis. We report here a complete anatomical distribution of the MCHR mRNA. We have found high levels of expression of MCHR mRNA in most anatomical areas implicated in control of olfaction, with the exception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
278
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(301 citation statements)
references
References 61 publications
21
278
0
2
Order By: Relevance
“…Conversely, a similar phenomenon could also be deduced for MCHergic synaptic innervation of ORX-containing neurons as many MCH receptors have been found in the LH. 17 Orexin -MCH synaptic interactions in feeding regulation To date, it has been demonstrated that ORX is involved in many physiological phenomena including food intake, 27 -30 sleep, 31 -33 endocrine function, 34 -37 narcolepsy 38,39 and regulation of body temperature, 40 muscle tone 41 and even pain sensation. 42 Likewise, MCH has been shown to play a role in food intake, 5 -7 endocrine function 43 -46 and pigmentation.…”
Section: Orexin -Mch Synaptic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a similar phenomenon could also be deduced for MCHergic synaptic innervation of ORX-containing neurons as many MCH receptors have been found in the LH. 17 Orexin -MCH synaptic interactions in feeding regulation To date, it has been demonstrated that ORX is involved in many physiological phenomena including food intake, 27 -30 sleep, 31 -33 endocrine function, 34 -37 narcolepsy 38,39 and regulation of body temperature, 40 muscle tone 41 and even pain sensation. 42 Likewise, MCH has been shown to play a role in food intake, 5 -7 endocrine function 43 -46 and pigmentation.…”
Section: Orexin -Mch Synaptic Interactionsmentioning
confidence: 99%
“…Given that both MCH-and ORX-containing neurons are involved in the regulation of food-intake behavior, one may imagine the possibility of direct synaptic relationships between them. Furthermore, ORX 16 and MCH 17 receptors have been found in the LH. The findings increase the possibility of reciprocal synaptic relationships between the ORX-and MCH-containing neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Pmch mRNA is upregulated after fasting or leptin deficiency (32, 50); third ventricle intracerebroventricular injections of MCH increase food intake and body weight (11,19,22,28,53); Pmch knockout mice are lean due to a decreased food intake and an increased metabolic rate (31, 59); and overexpression of MCH causes obesity (35). In rodents MCH binds to melanin-concentrating hormone receptor 1 (MCH1R), a G protein-coupled receptor expressed throughout the brain (7,33,55,56). MCH1R is particularly enriched in the nucleus accumbens shell (33,47,56), thus forming a potential hypothalamiclimbic circuit modulating the hedonic, or rewarding, aspects of feeding (16, 47).…”
mentioning
confidence: 99%
“…In the rodent brain, MCHR1 is expressed in areas important for feeding, learning and motivated behavior, integration of sensory and gustatory inputs, autonomic control, and arousal (22,23). MCHR1 mRNA is also expressed in the thyroid, kidney, adipose tissue, lung, testes, and tongue (23), whereas functional MCHR1 is also present in lymphocytes (12,14), insulin-producing cell lines (24), and mouse and human pancreatic islets (8).…”
mentioning
confidence: 99%